Prediction and explanation on adolescent aggression: a study protocol - Ahmad Fauzi, Fatimah; Mohd Zulkefli, Nor Afiah; Baharom, Anisah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Adolescent aggression is an important public health concern with escalating prevalence of juvenile cases and violence among these age groups including robbery, homicide, and gang fights. The objectives of this study protocol are to determine the biopsychosocial predictors and explore the contextual factors of adolescent aggression among secondary school students in Hulu Langat. Methods: Explanatory mixed method study design will be used, consist of quantitative cross-sectional study followed by basic qualitative study. Proportionate population sampling among Form 4 secondary school students from selected public secondary schools in Hulu Langat will be executed. Questionnaires will be distributed to 481 students on aggression as the dependent variable, and several independent variables: demographic (ethnicity, family income), biological (sex, head injury, nutritional deficiency, breakfast skipping), psychological (attitude and normative beliefs, personality trait, emotional intelligence), and social factors (family environment, single parent status, domestic violence, peer deviant affiliation, alcohol, smoking, substance abuse). Subsequently, participants with moderate to high aggression scores will be further explored on the contextual factors of adolescent aggression by in-depth interview. Multiple linear regression will be executed using SPSS to determine significant predictors whereas thematic analysis will be applied for qualitative data analysis on the context of adolescent aggression. Both findings will be further integrated and discussed to give comprehensive description on the phenomena. Conclusion: Better knowledge and understanding on adolescent aggression may generate new framework to drive more effective preventive strategies and unravel adolescent aggressive related Public Health problems.